"My child is missing": 911 calls in mysterious disappearances of children. (November 2022) - O'Donnell, Daniel E.; Shelton, Joy Lynn; Shaffer, Sarah A.; Isom, Adrienne; Bowlin, Jennifer; Wood, Ellen
Abstract: Calls to 911 serve as important pieces of information in cases where a child has gone missing. Because investigation of mysterious child disappearances can pose unique challenges for law enforcement, the current study examined the characteristics of reports in such cases. Specifically, the current study compared proposed indicators of deception in a sample of child disappearances in which caregivers had made true or false allegations in their initial reports. Results suggest that characteristics traditionally thought to be indicators of deception were not present in cases of caregivers who had falsely alleged abduction. Further, many indicators conceptualized in previous research on 911 calls were not present in the current sample which suggests that established criteria for analyzing deceptive calls may be dependent on crime type or may be unreliable indicators altogether. Implications for policy and practice are discussed. Highlights: Use of the 911 COPS Scale® for deception may exacerbate bias in some instances. This is the first study to examine deception in 911 calls in child disappearances. This study contradicts the deceptive indicators proposed in the 911 COPS Scale®. Future 911 call veracity research should use validated deception detection methods.